The relationship between the clinical characteristics of patients with alcohol use disorder and drinking motives - S. G. Klimanova; A. A. Berezina; A. V. Trusova; D. V. Podoliak; K. V. Rybakova; E. M. Krupitsky (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева)
Changes in the motivational structure are considered one of the central characteristics of Alcohol Use Disorder (AUD). The latest motivational models of AUD were developed based on recent neurobiological research findings. According to these models, three main drinking motives can be identified — drinking as a reward, as a relief, and as a habit.   The goal of the study was to explore the main differences in the psychological and clinical characteristics of patients with AUD depending on the predominant drinking motive.   For this study, 76 individuals (50 men (65.79 %), average age 42.25 ± 9.36 y. o. (М ± SD)) undergoing in-patient treatment for the symptoms of AUD were recruited. The following methods were used: clinical interview, UCLA Reward, Relief, Habit Drinking Scale, Penn Alcohol Craving Scale, Obsessive Compulsive Drinking Scale, Hospital Anxiety and Depression Scale, Snaith-Hamilton Pleasure Scale, Behavioral Activation Scale/Behavioral Inhibition Scale, and Cognitive Emotion Regulation Questionnaire. The participants were divided into three groups depending on their predominant drinking motive. The participants with the predominant “drinking as a habit” motivation reported using strategies of “refocusing on planning” and “positive reappraisal” significantly less often. At the same time, the intensity of “drinking as a habit” motive positively correlated with the severity of anxiety and depressive symptoms, and negatively — with the strength of the behavioral inhibition system. The participants with the “drinking as a reward” motivation reported having greater reward responsiveness as compared to the combined group of participants with the relief and habit drinking motives. The intensity of “drinking as a relief” motivation positively correlated with the severity of depressive symptoms. It was also noted that the participants, who did not identify the predominant drinking motive, reported having decreased levels of emotional and physical functioning and less frequent use of the certain adaptive emotional regulation strategies. In contrast with the previous studies, the relationship between the prevailing drinking motives and characteristics of drinking or the severity of AUD was not identified.